UJI EFISIENSI BUDI DAYA TUMPANGSARI TANAMAN KACANG BUNCIS (Phaseolusvulgaris L.) DENGAN SAWI PUTIH (Brassica juncea L.) PADA POLA TANAM YANG BERBEDA - Subhan Subhan; Oetami Dwi Hajoeningtijas; Agus Mulyadi Purnawanto (Universitas Muhammadiyah Purwokerto, 2016)
This research is to know at the result white mustard and intercropping green beans farm and to know the efficiency in using land in intercropping white mustard and green beans.This research was used randomize design method single factor, with 5 treatment suchas cropping patterns between white mustard and green beans repeated 3 times, so there were 15 experimental units. There are research treatment: T01: green beans monoculture control, T02: mustard monoculture control, T1: green benas line1 mustard line, T2: 2 green beanslines 1 mustard line, and T3: 1 green beans line 2 mustard lines. The observed variables: diameter crop, a fresh weight of white mustard, the number of green beans, and a fresh weight of green beans. The data was analyzed using F test, continued with BNJ test withextent error 5%. The result of the research showed that T02 treatment give the best effect on diamer mustard variable, T1 give the best effect on fresh weight mustard variable, T2 show the best effect on the number of green beans pod, and fresh weight green beans pod. Based on equity ratio of land, mustard and green beans planted using intercropping system showed that it more efficient than using monoculture system